2022
DOI: 10.1021/acs.jpcc.2c03541
|View full text |Cite
|
Sign up to set email alerts
|

Toward Metal-free Photocatalysis: Photochemical Regeneration of Organic Hydride Donors Using Phenazine-Based Photosensitizers

Abstract: Earth-abundant chromophores and catalysts are important molecular building blocks for artificial photosynthesis applications. Our team previously reported that metal-free hydride donors, such as biomimetic benzoimidazole-based motifs, can reduce CO2 selectively to the formate ion and that they can be electrochemically regenerated using the proton-coupled mechanism. To enable direct utilization of solar energy, we report here the photochemical regeneration of a benzoimidazole-based hydride donor using a phenazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…7 Inspired by the fact that biological systems follow a 2e − / 1H + -transfer concept instead of a typical chemical hydride (H − , which is equivalent to 2e − /1H + ) transfer for the regeneration step, recent investigations demonstrated that the regeneration of certain organic hydride compounds (AH) is indeed possible by the electrochemical approach via the proton-coupled electron-transfer process in the presence of a suitable proton source, 3a,8 or by photochemical approach using suitable photosensitizers (Figure 1b). 9 However, because electron-and proton-transfer events with the oxidized organic NADP + analogues are inherently involved, the still-existing key challenges with many organic systems are as follows: (i) facile irreversible dimerization of the one-electron reduced (electrochemically generated) radical species (A • ) prior to the desired reaction and (ii) difficult protonation step of the one-electronreduced radical species (A • ) for its (AH •+ ) further oneelectron reduction to form the hydride (AH). By improving the stability and basicity of the electrochemically generated organic radicals with proper structural modification and also by employing a suitable proton source with matching pK a values, the above limitations were overcome to a certain extent.…”
Section: ■ Introductionmentioning
confidence: 99%
“…7 Inspired by the fact that biological systems follow a 2e − / 1H + -transfer concept instead of a typical chemical hydride (H − , which is equivalent to 2e − /1H + ) transfer for the regeneration step, recent investigations demonstrated that the regeneration of certain organic hydride compounds (AH) is indeed possible by the electrochemical approach via the proton-coupled electron-transfer process in the presence of a suitable proton source, 3a,8 or by photochemical approach using suitable photosensitizers (Figure 1b). 9 However, because electron-and proton-transfer events with the oxidized organic NADP + analogues are inherently involved, the still-existing key challenges with many organic systems are as follows: (i) facile irreversible dimerization of the one-electron reduced (electrochemically generated) radical species (A • ) prior to the desired reaction and (ii) difficult protonation step of the one-electronreduced radical species (A • ) for its (AH •+ ) further oneelectron reduction to form the hydride (AH). By improving the stability and basicity of the electrochemically generated organic radicals with proper structural modification and also by employing a suitable proton source with matching pK a values, the above limitations were overcome to a certain extent.…”
Section: ■ Introductionmentioning
confidence: 99%
“…17 Hasegawa et al reported photochemical hydrodesulfonylation using a catalytic amount of BI + -1Nap-O − in the presence of stoichiometric NaBH 4 (Figure 1c). 21 Recently, Glusac 22 and our group 23,24 independently reported the photochemical regeneration of BIH (Figure 1d,e). Using photochemical regeneration, metal-free CO 2 reduction to formate was achieved (Figure 1e), 24 in which the excited state of the carbazole photosensitizer PS2 with high reducing capability 25−27 performed the first one-electron transfer in the two-electron reduction process of BI + -Me to BIH-Me.…”
Section: ■ Introductionmentioning
confidence: 87%
“…17 Hasegawa et al reported photochemical hydrodesulfonylation using a catalytic amount of BI + -1Nap-Oin the presence of stoichiometric NaBH4 (Figure 1c). 21 Recently, Glusac 22 and our group [23][24] independently reported the photochemical regeneration of BIH (Figure 1d,e). Using photochemical regeneration, metal-free CO2 reduction to formate was achieved (Figure 1e), 24 in which the excited state of the carbazole photosensitizer PS2 with high reducing capability [25][26][27] performed the first one-electron transfer in the two-electron reduction process of BI + -Me to BIH-Me.…”
mentioning
confidence: 94%